Evaluation of a short home blood pressure measurement in an outpatient population of hypertensives. (16th November 2016) - Di Monaco, Silvia; Rabbia, Franco; Covella, Michele; Fulcheri, Chiara; Berra, Elena; Pappaccogli, Marco; Perlo, Elisa; Bertello, Chiara; Veglio, Franco
ABSTRACT: Current guidelines suggest the use of home blood pressure monitoring (HBPM) as a method complementary to ambulatory blood pressure monitoring (ABPM) for the identification of arterial hypertension. A cross-sectional study was conducted to evaluate the accuracy of a short HBPM schedule compared with ABPM, and to evaluate to what extent HBPM can replace ABPM. A total of 310 patients who performed ABPM in our hypertension clinic were enrolled between November 2011 and June 2015. They performed a 4-day HBPM schedule, with two readings in the morning and two readings at night. Results showed a moderate correlation between HBPM and ABPM ( r = 0.59 for systolic blood pressure (SBP) and r = 0.72 for diastolic blood pressure (DBP)) and moderate diagnostic agreement (area under curve: 0.791 for SBP and 0.857 for DBP). No significant difference was found between first-day average and those of days 2–4. Diagnostic agreement between the two techniques was moderate, supporting the notion that HBPM cannot replace ABPM in the general population. However, we identified two HBPM thresholds, 123/75 and 144/87 mm Hg, through which subjects who may not require further ABPM can be identified.